Is It Primary Carcinoma or Lymphoma Breast: Re-emphasizing the Value of Tissue Diagnosis in a Challenging Case Presenting With Pulmonary Thromboembolism - Gurpreet Kaur Walia; Surjeet Dwivedi; Arijit Datta; Ramanjit Singh Akal (CHRISMED Journal of Health and Research)
Primary lymphoma of the breast is an uncommon entity with a prevalence of 1%–2% of non-Hodgkin’s lymphomas. Most of them are B-cell type (50% of all malignant breast lymphomas). We present the case of a 53-year-old female, who reported with 20 cm × 15 cm gradually progressive lump in the right breast for 2 months, involving the entire right breast. Positron emission tomography scan confirmed a metabolically active mass lesion in the right breast. Trucut biopsy of the lump revealed an infiltrating tumor arranged in diffuse sheets. Tumor cells were large with scant cytoplasm, high N:C ratio, and hyperchromatic nuclei. Immunohistochemistry showed CD20, bcl2, bcl6, and CD10 positive in tumor cells, whereas CD3 and MUM1 were negative. A final opinion of diffuse large B-cell lymphoma-germinal center type was given. The patient was managed with six cycles of chemotherapy with R-CHOP, every 3 weeks. She was followed up for a period of 1 year and remained asymptomatic.